Survey of data possession provability proving on cloud storage - Wei FU; Qing YE; Ze-mao CHEN; Xiao-ping WU (Tongxin xuebao)
Data possession provability allows cloud users to verify whether their data are still integrally preserved in Cloud Storage system,and whether they can obtain the data at anytime,anywhere.It is a challenging research problem of cloud storage security.A data possession proving model and its estimating criteria system were established.Three famous proving schemes were analyzed in detail.Six proving methods were compared from different aspects.Finally,some valuable future research issues and suggestions were pointed out as conclusion.